Dreams of the burning child: sacrificial sons and the father's witness - Miller, David Lee (Cornell University Press, 2018)
Cover -- Dreams of the Burning Child -- Title -- Copyright -- Dedication -- Contents -- Preface -- Introduction: The Body of Fatherhood -- 1 The Deified Father and the Sacrificial Son -- 2 Virgil's Aeneid: The History of a Wound -- 3 Witnessing as Theater in Shakespeare -- 4 Charles Dickens: A Dead Hand at a Baby -- 5 Jonson, Freud, Lacan: This Moving Dream -- 6 Mourning Patriarchy: A Return to the Crossroads -- Bibliography -- Index